13.5k views
2 votes
Whats the answer for 6b+7-2b=1+5b

User Zgirod
by
6.1k points

2 Answers

2 votes

Answer:

b=6

Explanation:

We have the expression
6b+7-2b=1+5b

We are to leave in one side of the expression all the terms that has b and in the other the terms that doesn't have b.


6b+7-2b=1+5b\\6b-2b-5b=1-7

We can apply common factor b in the left side, and resolve the subtraction in the right side.


b(6-2-5)=-6\\b(-1)=-6

Now divide both sides in (-1).


b(-1)=-6\\(b(-1))/((-1))=((-6))/((-1)) \\b=6

Then the answer of
6b+7-2b=1+5b is b=6.

User NiklasMH
by
5.5k points
7 votes


Solution,6b+7-2b=1+5b\quad :\quad b=6


Steps:


6b+7-2b=1+5b


\mathrm{Group\:like\:terms}, 6b-2b+7=1+5b


\mathrm{Add\:similar\:elements:}\:6b-2b=4b, 4b+7=1+5b


\mathrm{Subtract\:}7\mathrm{\:from\:both\:sides}, 4b+7-7=1+5b-7


\mathrm{Simplify}, 4b=5b-6


\mathrm{Subtract\:}5b\mathrm{\:from\:both\:sides}, 4b-5b=5b-6-5b


\mathrm{Simplify}, -b=-6


\mathrm{Divide\:both\:sides\:by\:}-1, (-b)/(-1)=(-6)/(-1)


\mathrm{Simplify}, b=6


\mathrm{The\:Correct\:Answer\:is\:b=6}


\mathrm{Hope\:This\:Helps!!!}


\mathrm{-Austint1414}

User Czaporka
by
5.8k points